Serum levels of novel brominated flame retardants (NBFRs) in residents of a major BFR-producing region: Occurrence, impact factors and the relationship to thyroid and liver function - Zhao, Xuezhen; Chen, Tian; Yang, Bin; Wang, Dejun; Sun, Wen; Wang, Yuwei; Yang, Xiaodi; Wen, Sheng; Li, Jingguang; Shi, Zhixiong (Ecotoxicology and environmental safety, 2021)
Five currently used novel brominated flame retardants (NBFRs) were determined in 172 serum samples collected from nonoccupational residents of a major BFR-producing region. All the 5 NBFRs presented high detection frequencies (DFs, >90%), and decabromodiphenyl ethane (DBDPE), a substitute of decabrominated diphenyl ethers (deca-BDE), was the most abundant NBFR. The levels of DBDPE were from <LOD to 1590 ng/g lw, with a median level of 32.5 ng/g lw. The median levels of other NBFRs were from 0.134 to 2.87 ng/g lw, which were at least 10 times lower than that of DBDPE. Moreover, a comparison to other studies showed that our results were significantly higher than studies conducted in background population. The levels of some NBFRs adjusted by serum lipid showed negative and significant correlation with BMI, whereas the difference disappeared when NBFRs levels were calculated based on serum volume. Certain NBFRs in female showed significantly higher concentrations than those in male. No significant effect of age, smoking habit, education level and children birth (in female) on serum NBFR levels was observed. The relationship between the serum levels of NBFRs and a series of thyroid/liver injury biomarkers was further analyzed to evaluate the health effects of these NBFRs to human being. Results showed that a 10-fold increment in the serum DBDPE level was associated with decreased total triiodothyronine (TT3) level (−0.037 nmol/L) [95% CI: −0.070, −0.003]， whereas serum pentabromoethylbenzene (PBEB) level was associated with increased total triiodothyronine (TT3) level (0.031 nmol/L) [95% CI: 0.001, 0.060]. For liver indicators, a 10-fold increment in the serum level of PBT was associated with decreased Ln aspartate aminotransferase/alanine aminotransferase (AST/ALT) level (−0.068) [95% CI: −0.129, −0.007]. A 10-fold increment in the serum level of BTBPE was associated with increased TBIL level (0.869 μmol/L) [95% CI: 0.175, 1.564], direct bilirubin (DBIL) level (0.231 μmol/L) [95% CI: 0.075, 0.388] and IDBIL level (0.638 μmol/L) [95% CI: 0.091, 1.185]. Our findings indicate that BFR production is posing heavy BFR contamination to surrounding environment and human being, and which might relate to thyroid disruption and liver injury. [Display omitted] •Serum levels of five NBFRs were measured in residents of a BFR-producing region.•All NBFRs presented high detection frequencies.•DBDPE showed predominance in NBFRs whereas its level was lower than that of PBDEs.•Serum NBFR levels were significantly correlated with some thyroid/liver biomarkers.